Electrochemically Induced Synthesis of Imidazoles from Vinyl Azides and Benzyl Amines - Vil’, Vera A.; Grishin, Sergei S.; Terent’ev, Alexander O. (Molecules (Basel, Switzerland), 2022)
An electrochemically induced synthesis of imidazoles from vinyl azides and benzyl amines was developed. A wide range of imidazoles were obtained, with yields of 30 to 64%. The discovered transformation is a multistep process whose main steps include the generation of electrophilic iodine species, 2H-azirine formation from the vinyl azide, followed by its reactions with benzyl amine and with imine generated from benzyl amine. The cyclization and aromatization of the obtained intermediate lead to the target imidazole. The synthesis proceeds under constant current conditions in an undivided cell. Despite possible cathodic reduction of various unsaturated intermediates with C=N bonds, the efficient electrochemically induced synthesis of imidazoles was carried out.